Quantitative Estimation of Oxidative Stress in Cancer Tissue Cells Through Gene Expression Data Analyses - Liu, Liyang; Cui, Haining; Xu, Ying (Frontiers in Genetics, 2020)
Quantitative assessment of the intracellular oxidative stress level is a very important problem as it is the basis for elucidation of the fundamental causes of systematic changes such as metabolic changes in diseased human cells, particularly cancer. However, the problem proves to be very challenging to solve in vivo because of the complex nature of the problem. Here a computational method is presented for predicting the quantitative level of the intracellular oxidative stress in cancer tissue cells. The basic premise of the predictor is that the genomic mutation level is strongly associated with the intracellular oxidative stress level. Based on this, a statistical analysis is conducted to identify a list of enzyme-encoding genes, whose combined expression levels can well explain the mutation rates in individual cancer tissues in the TCGA database. We have assessed the validity of the predictor by assessing it against genes that are known to have anti-oxidative functions for specific types of oxidative stressors. Then the applications of the predictor are conducted to illustrate its utility.